TiO2 Photocatalytic Degradation of Methylene Blue Using Simple Spray Method. (August 2019) - Utami, F D; Rahman, D Y; Margareta, D O; Rahmayanti, H D; Munir, R; Sustini, E; Abdullah, M
Abstract: The present work focused on the effects of TiO2 in degrading organic wastewater. Technical TiO2 of anatase crystalline phase was used. TiO2 photocatalyst showed a powerful result in destroying organic effluent. Spray coating was conducted to immobilize the TiO2 particles onto the plastic buffer followed with heat-treatment process. As a result, 30 mL of 25 mg L −1 methylene blue (MB) used in the photocatalyst test was sucessfully degraded after 4 hours of irradiation. Repetitive use of the TiO2 films still has a great photodecomposition ability of removing 99% of the organic contaminant after 5 times use.